Humoral immune responses against SARS-CoV-2 Spike variants after mRNA vaccination in solid organ transplant recipients - Alexandra Tauzin; Guillaume Beaudoin-Bussières; Shang Yu Gong; Debashree Chatterjee; Gabrielle Gendron-Lepage; Catherine Bourassa; Guillaume Goyette; Normand Racine; Zineb Khrifi; Julie Turgeon; Cécile Tremblay; Valérie Martel-Laferrière; et al. (iScience, 2022)
Summary: Although SARS-CoV-2 mRNA vaccination has been shown to be safe and effective in the general population, immunocompromised solid organ transplant recipients (SOTRs) were reported to have impaired immune responses after one or two doses of vaccine. In this study, we examined humoral responses induced after the second and the third dose of mRNA vaccine in different SOTR (kidney, liver, lung, and heart). Compared to a cohort of SARS-CoV-2 naïve immunocompetent health care workers (HCWs), the second dose induced weak humoral responses in SOTRs, except for the liver recipients. The third dose boosted these responses but they did not reach the same level as in HCW. Interestingly, although the neutralizing activity against Delta and Omicron variants remained very low after the third dose, Fc-mediated effector functions in SOTR reached similar levels as in the HCW cohort. Whether these responses will suffice to protect SOTR from severe outcome remains to be determined.